2010
DOI: 10.2353/ajpath.2010.090960
|View full text |Cite
|
Sign up to set email alerts
|

Lack of a Major Role of Staphylococcus aureus Panton-Valentine Leukocidin in Lower Respiratory Tract Infection in Nonhuman Primates

Abstract: Panton-Valentine leukocidin (PVL) is a two-component cytolytic toxin epidemiologically linked to community-associated methicillin-resistant Staphylococcus aureus (CA-MRSA) infections , including serious invasive infections caused by the epidemic clone referred to as strain USA300. Although PVL has long been known to be a S. aureus virulence molecule in vitro, the relative contribution of this leukotoxin to invasive CA-MRSA infections such as pneumonia remains controversial. We developed a nonhuman primate mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
39
0
4

Year Published

2011
2011
2016
2016

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 48 publications
0
39
0
4
Order By: Relevance
“…In contrast, PVL may contribute to S. aureus persistence in a model of osteomyelitis (Table 1) (215). Additional studies in primates were unable to uncover a role for PVL in a pneumonia model (216). The discrepancy in virulence characteristics associated with pneumonia in rabbits and primates likely stems from the fact that primate PMNs are also relatively insensitive to the lytic functions of the toxin (200).…”
Section: Luksf-pv (Pvl)mentioning
confidence: 89%
“…In contrast, PVL may contribute to S. aureus persistence in a model of osteomyelitis (Table 1) (215). Additional studies in primates were unable to uncover a role for PVL in a pneumonia model (216). The discrepancy in virulence characteristics associated with pneumonia in rabbits and primates likely stems from the fact that primate PMNs are also relatively insensitive to the lytic functions of the toxin (200).…”
Section: Luksf-pv (Pvl)mentioning
confidence: 89%
“…A recent study performed vaccination experiments using LukS and/or LukF before infection with USA300 and disclosed improved survival in vaccinated mice, suggesting that PVL significantly contributes to S. aureus pathogenesis (58). Arguing that mouse models might not be ideal to study the in vivo role of PVL, Olsen et al (59) infected nonhuman primates with USA300 and isogenic PVL deletion-mutant strains and ultimately did not identify a major role for PVL in aggravating pneumonia in vivo. Nevertheless, no previous report studied the precise innate immune mechanisms associated with PVL.…”
Section: Discussionmentioning
confidence: 99%
“…Introduction of PVL into a laboratory S. aureus strain changed the expression of other virulence factors (143), but deletion of PVL from the USA300 and USA400 clinical isolates had no influence on global gene expression (147). Experiments on mice and rabbits have usually confirmed a role for PVL in virulence (143,(145)(146)(147)(148)(149)469), whereas studies using rats and primates, and occasionally mice and rabbits, have not identified a role for PVL in infection (155,345,470,471). Given the relative insensitivity of mouse and rat PMNs to PVL, rabbits appear to be a better model for studying the effects of PVL, as their PMNs are more sensitive to PVL, more closely resembling the human situation (145).…”
Section: Cautionary Notesmentioning
confidence: 99%